Food Hygienic Practices and Safety Measures among Street Food Vendors in Zanzibar Urban District. Issue 4 (30th June 2020) - Hassan, Jamila K.; Fweja, Leonard W.T.
Abstract : The purpose of this descriptive cross‐sectional survey study was to assess the hygiene and safety precautions implemented by street food vendors in the Urban district of Zanzibar. The study involved 265 food vendors with immobile food vending sites. An organized researcher‐executed questionnaire developed based on World Health Organization essential requirement for the safety of street‐vended foods was used in data collection and complemented with observation. Data on environmental hygiene of the surveyed vending sites indicated that <50% of the sites had both washbasin and soap in place and only 50.2% and 42.6% vending sites had waste bin and/or refuse sites respectively. Adherence to safe food handling practices were reflected in adequate protection of food from flies and dust (40.8%), cold storage of food (28.3%), saving food hot or reheating before sale (35.1%), dishing out food with spoon/ladle (53%) and food covering (57.4%). Hygienic and sanitary practices among food vendors demonstrated the following levels of adherence: washing hands with soap after toilet use (always 33.2%, sometimes 46.8%), washing hands with soap prior to preparing food (always 63%, sometimes 34%), keeping clean fingernail (98.5%), protection of hair (33.6%) and use of apron (29%). The results indicate poor environmental sanitation and waste handling practices, moderate adherence to food handling practices, safety measures and hygiene. Based on the results it is suggested that food safety and hygiene training should be a prior condition for starting a food‐vending venture and be complemented with regular monitoring. GRAPHICAL ABSTRACT: